Assessment of Students' Oral Communicative Competence in English Through a Web Conferencing Platform - María de los Milagros Cruz-Ramos; Luz Edith Herrera-Díaz (Universidad Nacional de Colombia, 2022)
This manuscript reports on a study carried out at a public university in southeast Mexico aimed to determine whether changes in the instructional design of an online English course benefit students' oral communicative competence. The research followed a quantitative quasi-experimental design that involved two groups of students. One of them took a modified version of an online English II course that provided contextualized instruction of the syllabus language topics. This group's communicative competence was assessed online, which represented a major shift from the face-to-face assessments typically delivered to online groups. The results showed that online assessment is possible, and also that students' communicative competence improved and was directly related to the intervention.